2005
DOI: 10.1007/s00421-005-1350-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between breath-hold time and physical performance in patients with cystic fibrosis

Abstract: Rehabilitation including physiotherapy is an important part of the treatment used to help improve the quality of life of patients with cystic fibrosis (CF). The aim of this study was to determine the value of the breath-hold time as an index of exercise tolerance in patients with CF. Eighteen patients in different states of CF were included. The breath-hold time was measured in all patients. The fitness level was assessed by means of a progressive exercise test on a cycle-ergometer. During the test, oxygen upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…Most forms of Cystic Fibrosis (CF) induce an impairment of the ventilatory function, characterized by an obstructive syndrome induced by mucus retention and inflammation of the airways . Thus, several changes of breathing pattern at rest and during exercise characterized by a more rapid and shallow breathing and an increased ventilatory response have been highlighted both in adults and in children with cystic fibrosisin comparison with healthy population …”
Section: Introductionmentioning
confidence: 99%
“…Most forms of Cystic Fibrosis (CF) induce an impairment of the ventilatory function, characterized by an obstructive syndrome induced by mucus retention and inflammation of the airways . Thus, several changes of breathing pattern at rest and during exercise characterized by a more rapid and shallow breathing and an increased ventilatory response have been highlighted both in adults and in children with cystic fibrosisin comparison with healthy population …”
Section: Introductionmentioning
confidence: 99%
“…Normal BMI values were between 20 and 24.9 Kg/m². Obesity was defined by a BMI ≥ 30 Kg/m² ( Barnai et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that this test is an interesting tool to detect asthmatic subjects with a poor perception of dyspnea, which is a risk factor for fatal asthma ( Nannini et al, 2007 ). In adult subjects with cystic fibrosis, MVIBHT is correlated with oxygen consumption at the anaerobic threshold, providing information about the exercise capacity of these subjects ( Barnai et al, 2005 ).…”
mentioning
confidence: 99%
“…La kinésithérapie est le plus souvent utilisée au niveau respiratoire, afin de drainer le mucus et désencombrer les patients. La qualité de vie chez les patients atteints de mucoviscidose repose principalement sur la condition physique et la fonction pulmonaire [1]. L'inactivité physique peut aggraver la maladie.…”
Section: Introductionunclassified
“…Pour calculer la consommation d'oxygène à partir du seuil anaéro-bique la formule est : 5,53 + 0,42 Â BHT et pour calculer la capacité d'exercice à partir du seuil anaérobique, la formule est : 0,56 + 0,38 Â BHT. Cette méthode est non invasive contrairement aux traditionnels tests d'effort[1], ce qui pré-sente un avantage. L'article de Gruber et al de 2011 s'intéresse à l'état de forme initial des patients à travers leur consommation d'oxygène (V'O 2 ).…”
unclassified